Histological ovarian features and hormonal determinations in assigned females at birth transgender individuals according to different testosterone preparations - Borrás, Aina; Barral, Yasmina; Fabregues, Francesc; Casals, Gemma; Mora, Mireia; Orois, Aida; Méndez, Marta; Saco, Adela; Goday, Anna; Manau, Dolors (Frontiers in Endocrinology, 2024)
Introduction: Distinct androgen formulations have been used as gender-affirming hormone treatment, but little is known about the specific changes that may occur in the ovary depending on the testosterone preparation used. The study aims to evaluate the histological modifications of the ovarian tissue and the hormonal changes after gender-affirming surgery based on the testosterone preparation employed, such as testosterone cypionate or undecanoate.Design: Unicenter transversal cohort study.Materials and methods: Sixty transmasculine persons before and after gender-affirming surgery. A histological examination of the ovaries was conducted, including the follicular population and the characterization of the ovarian stroma. Hormonal status (testosterone, estradiol, FSH, and LH) were also assessed before and after the procedure.Results: The median age of participants was similar between the two groups (27.9 vs. 26.7 years, p = 0.27). There were no differences in all hormonal determinations before gender-affirming surgery between the groups. After surgery, FSH levels increased significantly, especially in the testosterone undecanoate group compared to the cypionate group (72.3 vs. 38.3 U/L, p = 0.02), consistent with LH determinations (43.0 vs. 23.4 U/L, p = 0.02). However, no regimen modification was required for any individual. No statistical differences were observed in any parameter concerning the follicular population, nor were there any variances in the thickness of the tunica albuginea (p = 0.85) or the proportion of luteinized stromal cells. Nevertheless, there was a tendency toward increased luteinization in the testosterone cypionate group (88.2% vs. 76.9%, p > 0.05).Conclusions: In a cohort of transmasculine individuals using different androgen preparations, histological analysis of ovarian tissue revealed comparable findings. Both groups exhibited similar follicular populations and comparable modifications in stromal tissue. However, significant differences were observed in hormonal profiles, although no modification in testosterone dosage was needed.